(untitled) (Oxford, 2012)
IELTS Foundation Second Edition retains all of the best elements of the original course. This includes clear links to exam sections and incorporates the changes that have been made to the IELTS exam. It is a 12-unit course aimed at training students within an IELTS band of 4-5.5 in the skills required to increase their score.
Keywords: English language,English language,Tiếng Anh; Textbooks for foreign speakers,Examinations, questions, etc.,Giáo trình dành cho người nước ngoài